F63 Preliminary results from Q-MOTOR/Q-COG analyses in the repair-hd study. (September 2018) - Schubert, Robin; Rosser, Anne; Bachoud-Lévi, Anne-Catherine; Craufurd, David; Reilmann, Ralf
Abstract : Background: The Q-Motor assessment battery has been designed to quantitatively measure motor deficits and progression for use in clinical studies. The assessments have shown to be able to detect subtle motor changes reliably and with absence of rater induced bias. The Q-Cog assessment battery adds assessments with an increased cognitive share, with the goal to achieve a comparable level of sensitivity for cognitive deficits of participants. The EUFP 7 funded Repair-HD (www.repair-hd.eu) study is the first to implement the Q-Cog assessments for exploratory analyses. Aims: To identify sensitive and robust measures to quantitatively track cognitive progression in HD. Methods: The analyzed data set includes 128 participants (52 controls, 76 HD manifest TFC stage I or II, mean age: 51 (22–78), female: 54). Statistical analyses were performed using generalized linear mixed models in R. Motor and cognitive tests were included in the assessment battery. Cognitive Assessments: Force Matching: To match a visually presented force by applying pressure on a force transducer. Blinded Force Matching: Reproduction of presented force by memory (without visual feedback). Morse Code Mimicry: To tap an acoustically presented Morse code (series of short and long beeps) on a force transducer. Trail Making: Connect dots numbered from 1 to 25 (test A) or alternating digits and letters 1, A, 2, B … to 13 (test B), using a 6-axis motion tracker pen. Motor Assessments: Speeded Finger Tapping, Metronome Tapping, Grasping & Lifting, Spiral Drawing. Results: Highly significant differences between control and manifest group could be found for various variables in all performed tests. Assessment of of cognitive function using the tests described is feasible and test-retest assessment shows low variability. Conclusion: While results from motor tasks reproduce previous findings, the cognitive assessments, too, are able to discriminate control groups from manifest population robustly. The long-term longitudinal performance, robustness and possible redundancy of the novel variables is yet to be explored. Further analysis is required to separate motor and cognitive effects through ratios of variables of the different assessments.